2015
DOI: 10.1016/j.sbspro.2015.01.803
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulation and Academic Self-efficacy of Czech University Students

Abstract: The paper presents findings on self-regulatory behavior in Czech adults, as measured by SRQ-CZ, an instrument originally developed by Brown et al. (1999), and on self-efficacy in learning as measured by SEQ, an instrument developed by Jakešová (2014). The two results correlated low, which indicates that SRQ-CZ measures the generic ability while the SEQ measures domain specific beliefs. As expected, the scores on positive dimensions of SRQ-CZ (Goal Orientation and Decision Making) were above the midpoint of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 12 publications
1
11
1
8
Order By: Relevance
“…Regarding self-efficacy for learning, students showed a moderate sense of self-efficacy for learning. Such result differed from those from studies that found a higher sense of selfefficacy among university students (Jakešováa et al, 2015;Erb and Drysdale, 2017). As having positive attitudes toward learning and adaptive beliefs about one's own ability to perform academic tasks successfully are factors that influence academic achievement and future professional life, a higher sense of efficacy for learning would be desirable among students in the sample (Bandura, 1997;Pajares and Olaz, 2008).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Regarding self-efficacy for learning, students showed a moderate sense of self-efficacy for learning. Such result differed from those from studies that found a higher sense of selfefficacy among university students (Jakešováa et al, 2015;Erb and Drysdale, 2017). As having positive attitudes toward learning and adaptive beliefs about one's own ability to perform academic tasks successfully are factors that influence academic achievement and future professional life, a higher sense of efficacy for learning would be desirable among students in the sample (Bandura, 1997;Pajares and Olaz, 2008).…”
Section: Discussioncontrasting
confidence: 70%
“…Self-efficacy beliefs and strategic and self-regulated learning are malleable and can be fostered through educational intervention (Bandura, 1978(Bandura, , 1986Zimmerman and Schunk, 2011;Zimmerman, 2013;Jakešováa et al, 2015;Erb and Drysdale, 2017;Weinstein and Acee, 2018). Teachers' roles are of paramount importance in fostering student development in these areas across all segments of schooling.…”
Section: Introductionmentioning
confidence: 99%
“…Self-regulation arises in the context of the monitorization process and is related to student research self-monitoring and self-efficacy (Jakesová, Kalenda & Gavora, 2015;Zimmerman, 2000). It is important for the doctoral student to define objectives (to take ownership of the doctoral project as its author), to plan the learning and research process, to monitor the achievement of the predefined objectives, to fulfil the proposals he/she has planned (to execute), to reformulate strategies, to manage the time and the emotions, to complete their degree.…”
Section: Self-regulation Self-assessment and Doctoral Research Self-mentioning
confidence: 99%
“…In the language of the selfregulation theory, they favour to execute self-direction strategies. Self-direction is an important component of self-regulation of behaviour and learning, usually accompanied with goal orientation, decision making and impulse control of the learner (Jakešová et al, 2015;Gavora et al, 2015). It is obvious that the participants have personal standards of success which is based on discrepancy reduction between their effort and the product of learning.…”
Section: Extractmentioning
confidence: 99%